1.
a) ^ 1 9/16 * (-2)' +1,2* 5/12
b)2 1/2 - 1/2 * 3^3 3/8 +2-'
c)(3/4)-' - (-1 1/3)':0,9
d)0,8* 3/2"- (-2)"/4 *0,1
e)(1 1/3)'*(-1/3)-" - 1,9`* 3-'
historia:
^ - pierwiastek
/ - kreska ułamkowa
' - do kwadratu
3^- pierwiastek trzeciego stopnia
-' - minus 1 u góry
" - do sześcianu
-" - minus 2 u góra
` - oznacza 0 u góry

1

Odpowiedzi

2009-10-05T15:38:43+02:00
A) √1 9/16 * (-2)² +1,2* 5/12 = √25/16*4+½ = 5/4*4+½ = 5½

b)2½ - ½ * ∛3 3/8 +2⁻¹ = 2½-½*∛27/8+½ = 2½-½*3/2+½ = 2½-¾+½ = 2¼

c)(¾)⁻¹ - (-1⅓)²:0,9 = 4/3-(4/3)²:0,9 = 4/3-(-16/9):9/10 = 4/3-(-16/9)*10/9 = 4/3+160/81=108/81+160/81 = 268/81 = 3 25/81

d)0,8* 3/2³- (-2)³/4 *0,1 = 8/10*27/8-(-8)/0,4 = 2,7-(-20)=2,2+20=22,7

e)(1⅓)²*(-⅓)⁻² - 1,9⁰* 3⁻¹ = (4/3)²*(-3)²-1*⅓ = 16/9*9-⅓==16-⅓=15⅔